PROPERTIES OF (γ, γ′)-SEMIOPEN SETS - Carpintero, C.; Rajesh, N.; Rosas, E. (Italian Journal of Pure and Applied Mathematics, 2013)
In this paper, we introduce and study the concept of (γ, γ′)-θ-semiconnectedness and (γ, γ′)-θ-semicomponents using (γ, γ′)-θ-semiopen sets.